A comprehensive analysis of G-protein-signaling modulator 2 as a prognostic and diagnostic marker for pan-cancer - Hu, Lei-Ming; Ou, Xue-Hai; Shi, Shao-Yan (Frontiers in Genetics, 2022)
Background: G-protein signaling modulator 2 (GPSM2) is involved in maintaining cell polarization and regulating cell cycle, and recent studies have shown that it is highly expressed in various tumors, but its pan-cancer analysis has not been reported. Methods: First, we analyzed the differential GPSM2 expression in normal and cancer tissues by the Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx) and Human Protein Atlas (HPA) databases and investigated its expression effect on the survival of cancer patients by gene expression profiling interactive analysis 2 (GEPIA2). Second, we analyzed the GPSM2 phosphorylation level using the clinical proteomic tumor analysis consortium (CPTAC) dataset. In addition, we investigated GPSM2 gene mutations in human tumor specimens and the impact of gene mutations on patient survival. Finally, we analyzed the relationship between GPSM2 expression and cellular immune infiltration through the TIMER 2.0 database. Meanwhile, the possible signaling pathway of the gene was analyzed by the Gene Ontology (GO)| Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway to explore its potential mechanism. Results: GPSM2 is overexpressed in most cancers, which leads to reduced overall survival (OS) and disease-free survival (DFS) in patients. The results of phosphorylation analysis suggest that tumor development involves a complex GPSM2 phosphorylation process. We identified GPSM2 mutation loci with the highest frequency of mutations in uterine corpus endometrial carcinoma (UCEC), and this mutation increased progression-free survival (PFS) and OS in UCEC patients. Finally, we found that the role of GPSM2 in tumors may be associated with cellular immune infiltration. GO|KEGG pathway analysis showed that the enrichment pathways were mainly "mitotic nuclear division", "chromosome segreation" and "spindle". Conclusions: Our pan-cancer analysis provides a comprehensive overview of the oncogenic roles and potential mechanisms of GPSM2 in multiple human cancers.